2021
DOI: 10.1126/sciadv.abe8873
|View full text |Cite
|
Sign up to set email alerts
|

Hormone autocrination by vascularized hydrogel delivery of ovary spheroids to rescue ovarian dysfunctions

Abstract: The regeneration potential of implantable organ model hydrogels is applied to treat a loss of ovarian endocrine function in women experiencing menopause and/or cancer therapy. A rat ovariectomy model is used to harvest autologous ovary cells while subsequently producing a layer-by-layer form of follicle spheroids. Implantation of a microchannel network hydrogel with cell spheroids [vascularized hydrogel with ovarian spheroids (VHOS)] into an ischemic hindlimb of ovariectomized rats significantly aids the recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…Further, the perfusion connection of the microchannel network with in‐growing host vessels sets up routes for cancer cells and soluble factors to move into the circulatory system, as shown in our previous studies. [ 3 , 25 ] In this manner, cancer propagation into other organs through the circulatory track can be monitored while examining systemic side effects of the drug when injected through IP, as used in this study, or even intravenous (IV) routes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the perfusion connection of the microchannel network with in‐growing host vessels sets up routes for cancer cells and soluble factors to move into the circulatory system, as shown in our previous studies. [ 3 , 25 ] In this manner, cancer propagation into other organs through the circulatory track can be monitored while examining systemic side effects of the drug when injected through IP, as used in this study, or even intravenous (IV) routes.…”
Section: Discussionmentioning
confidence: 99%
“…The model of OC tissueoid implantation into ischemic hindlimbs of mice was used to establish a new model of systemic cancer response, as reported in previous studies. [ 3 , 25 ] The OC tissueoid was labeled with a fluorescent dye solution (Vybrant DiD Cell‐Labeling Solution, Thermo Fisher Scientific, Waltham, MA, USA) in culture medium (1:200 dilution) at 37 °C with 5% CO 2 for 1 h. The upper and lower points of the femoral artery were ligated using a 4‐0 silk suture (Ethicon, Somerville, NJ, USA), and the femoral artery was dissociated and separated from the vein, followed by implantation of OC tissueoid into hindlimb muscle. Cancer propagation from the implantation site before and after OC tissueoid harvest was visualized using an in vivo imaging system (IVIS, PerkinElmer, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Isolated follicles may be transplanted into patients instead of ovarian tissue, and the storage and culture of follicles in vitro is the foundation for artificial ovary feasibility (See The Application of Hydrogels in Follicle Culture for details). Studies have shown that the transplantation of artificial ovaries promotes the survival and maturation of follicles in vivo (Rios et al, 2018), improves local vascularization (Rajabzadeh et al, 2020), and restores hormones to a level at which the endometrium regenerates (Yoon et al, 2021).…”
Section: The Application Of Hydrogels In Pofmentioning
confidence: 99%
“…In obstetrics and gynecology, the main application of hydrogel is in the treatment of POF and IUA. Hydrogels have been studied for ovarian tissue transplantation and artificial ovary, and the three-dimensional structure of hydrogels provides support for follicle growth and morphology maintenance, making ovarian tissue and follicle autologous transplantation possible (Shikanov et al, 2009;Yoon et al, 2021). The application of hydrogels in IUA is mainly focused on drug delivery and stem cell delivery therapy (Mettler et al, 2008;Xue et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the surrounding environment is important, and 3D cell deposition is necessitated. Tissue engineering technology enables the fabrication of various types of engineered organs such as the pancreas, liver, kidney, ovary, bladder, cornea, muscle, skin, vessel, esophagus, and the like using SCs and biomaterials (Figure 2) [127][128][129][130][131][132][133][134][135][136][137]. Although numerous hurdles (i.e., low cell survival, immune response, and insufficient functions) remain to be overcome, many studies have revealed the effectiveness of engineered tissue transplantation as a novel regeneration method [138,139].…”
Section: D Bioprinting Using Ecm-based Bioinksmentioning
confidence: 99%